(untitled) (European Journal of Interdisciplinary Studies, 2017)
Indonesia is a large and socially heterogeneous country because it covers more than 1,340 ethnic groups. The country is rich of various cultural traditions. The diversity of cultural traditions in Indonesia is interestingly studied both as a material of scientific study and as an source to formulate appropriate socio-economic development policy approaches. One of the regions/islands in Indonesia is Papua, which is located in the eastern part of Indonesia. In this region there are more than 500 ethnic groups. Ethnic groups in Papua, is the most traditional ethnic group compared to those in Indonesia. One tradition that is still strongly held in Papua is tribal war. Therefore it is a very interesting phenomenon studied in terms of social science, especially communication science. The symbolic interactionism perspective as a communication approach is used in this study to explain how the communication process occurs in traditional war process between tribes, both in the internal communication of tribes and communications between tribes. This study describes the phenomenon of war between tribes according to the view or the consciousness and subjective meaning of traditional/indeginuous people in Timika, in accordance with the phenomenology tradition that is used in this research. The findings of this study are illustrates the process of communication, beginning from preparation of war, the implementation of war, as well as post-war process. Communication processes that occur either through verbal or non-verbal language are full of distinctive symbols. The conclusion of this finding is that tribal war as a social phenomenon is a communication process, and can be solved by the parties by means of communication. These findings could have implications for the importance of policies to develop communication approaches among traditional tribes in Papua, in order to increase the understanding among them, which in turn will reduce the level of conflict between them.